2004
DOI: 10.1021/ma049573c
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Molecular Motion in Low Molecular Weight Polystyrene

Abstract: The variations with temperature of the viscosity, η, and the relaxation times for various low molecular weight, unentangled polystyrenes (PS) are analyzed. We find that the temperature dependence of η does not directly reflect the behavior of the global chain modes. Depending on molecular weight and temperature, η can exhibit a stronger temperature dependence than even the local segmental modes. However, this is only a consequence of the strong temperature dependence of the recoverable compliance J s. The Rous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…[67] Furthermore, low-molecular-weight polymers should have smaller coupling effects for lower entanglement degrees, but the transitional diffusion of polymers with low molecular weight is not enhanced. [68,69] The slower processes were rarely thought to be connected to molecular weight. Recently, Roland et al [70] found that the T g and T g normalised relaxation time of polybutadienes (PB) varied monotonically with the number-average molecular weight.…”
Section: Dependence Of Molecular Weightmentioning
confidence: 99%
“…[67] Furthermore, low-molecular-weight polymers should have smaller coupling effects for lower entanglement degrees, but the transitional diffusion of polymers with low molecular weight is not enhanced. [68,69] The slower processes were rarely thought to be connected to molecular weight. Recently, Roland et al [70] found that the T g and T g normalised relaxation time of polybutadienes (PB) varied monotonically with the number-average molecular weight.…”
Section: Dependence Of Molecular Weightmentioning
confidence: 99%
“…(16). This is because, in the application of the CM to polymer dynamics and viscoelasticity [25,191,202,205,206,208,209,295], the normal modes and the local segmental mode have the same primitive monomeric friction coefficient 0 ðT À1 V Àg Þ. Based on this, the breakdown of thermorheological simplicity of the viscoelastic spectrum of amorphous polymers discussed in Section III, (paragraph 4), was explained based on the difference between the coupling parameter n a and n n of the local segmental mode and the normal modes, respectively.…”
Section: Relation Between the Activation Enthalpies Of S Jg And S mentioning
confidence: 99%
“…All rheological measurements were done at 25 °C. 32 The crossover from Newtonian flow to shear thinning behavior occurs at a shear rate given by 33 (2) This is the approximate value of the minimum shear rate necessary to ensure disentanglement by flow.…”
Section: Introductionmentioning
confidence: 99%